Diffusion Tensor Imaging Features of the Auditory Pathways in Patients With Vestibular Schwannoma After Gamma Knife Radiosurgery - ÇEŞME, DİLEK HACER; ÇEŞME, DİLEK HACER; ALKAN, ALPAY; ALKAN, ALPAY; GÜLTEKİN, MEHMET ALİ; GÜLTEKİN, MEHMET ALİ; SARI, LÜTFULLAH; SARI, LÜTFULLAH; Alkan, Gokberk; KAYA, AHMET; KAYA, AHMET; MAYADAĞLI, Alpaslan; et al. (My University, 2021)
Objective In this study, we aimed to investigate whether there is any change in diffusion tensor imaging (DTI) parameters in ipsilateral and contralateral auditory pathways after Gamma Knife radiosurgery (GKR) in patients with vestibular schwannoma (VS) and the relationship between radiosurgery variables. Methods Sixty-six patients were evaluated with MRI and DTI before and after GKR. The apparent diffusion coefficient (ADC) and fractional anisotropy (FA) were measured from the bilateral lateral lemniscus (LL), inferior colliculus (IC), medial geniculate body (MGB), and Heschl's gyrus (HG). Results There was no significant difference in ADC and FA values obtained from bilateral LL, IC, and MGB before and after radiosurgery. However, there was a significant difference between pretreatment and post-radiosurgery contralateral HG ADC values. The ADC values obtained from the contralateral HG and IC positively correlated with the duration after radiosurgery. As the duration after radiosurgery increases, the difference between the ADC values obtained from ipsilateral and contralateral HG also increases. Conclusion The high ADC values in the contralateral HG after radiosurgery may indicate microstructural alterations such as demyelination and axonal loss. Radiation exposure doses to the brainstem and cochlea are the most important factors that can cause microstructural damage to the auditory pathways. When planning radiosurgery, extreme care should be taken to prevent the harmful effects of radiation on the auditory pathways.
Keywords: auditory pathways; diffusion tensor imaging; gamma knife radiosurgery; radiosurgery; vestibular schwannoma